ANALISIS LAJU KOROSI DAN SISA UMUR PAKAI PADA TANGKI TIMBUN BAHAN BAKAR DI PLTD HARUKU - Marasabessy, Salman; Karyani, M.Said; Lilipaly, Eka R. M. A. P. (Jurusan Teknik Mesin, 2024)
Corrosion resistance is the most important criterion in determining both the service life (remaining life) and operational reliability of equipment in the oil and gas industry. So it is very important to monitor the performance of every equipment in this industry. As with storage tanks, during long periods of operation and use, performance will likely decrease or could be said to experience thinning, thereby posing a danger to the thickness and remaining life of the ultrasonic thickness measuring instrument. differences in steel thickness data from the beginning and the thickness carried out by researchers. The data collected is also data that determines the minimum value for steel thickness in order to calculate the useful life of the media that will be examined by tanks that carry out measurements and maintenance using API 653 standards. Take measurements at several points 1. From the results of the analysis of the 100KL Tank located at PLTD HARUKU Using the UTG-90 Ultrasonic Thickness Gauge tool for plate thickness in August 2024, the results were that for Course 1 3.3, Course 2 3.4, Course 3 4.1, and Course 4 4.0 and the remaining tank life for each -Course 1, Course 2, Course 3 and Course 4 respectively are 11.26 years, 11.86 years, 32 years, 27.8 years1. The 100KL tank needs to undergo a Remaining Life Assessment (RLA) in 2028 and a regular tank inspection routine must be carried out to prevent leaks in the tank at least once every 4 years. Keywords : Tangki, corrosion, remaining life, tank thickness